Functional Heads in the Dholuo Determiner Phrase - Agalo, Jerry; Midigo, Jackton Otieno (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
This paper focuses on functional heads existing in a Dholuo DP. The notion of functional heads in the extended Projection of the CP (Complementizer Phrase) has led to a new approach in the analysis of projections in syntactic theory. The objective was to identify the functional elements in the Dholuo DP, analyze the functional elements and explain their occurrence. The study used Government and Binding theory which enables us to analyze the functional heads. The study also used descriptive research design to analyze collected data. The data was collected from 40 informants aged 35 years to 50 years; which was a sample from population of Dholuo speakers living in Homa Bay County around Lake Victoria. Data collected had sentences with Dholuo DPs. The study found eleven elements commonly occurring in Dholuo DP. These elements form the structure of Dholuo DP and can be categorized as lexical and functional heads. The lexical elements identified in the Dholuo DPs are: Nouns, Adjectives, prepositional phrases and genitive phrases. The functional elements identified included: Pronouns, article affixes, demonstratives, possessives, quantifiers, numerals, and relative clauses. In Dholuo, genitive phrases have prepositions acting as possessives. Relative clauses on the other hand, contain relative word, verb, pronoun, preposition and demonstratives.